Management of patients with diabetes and obesity in the COVID-19 era: Experiences and learnings from South and East Europe, the Middle East, and Africa. (February 2021) - Giorgino, Francesco; Bhana, Sindeep; Czupryniak, Leszek; Dagdelen, Selcuk; Galstyan, Gagik R.; Janež, Andrej; Lalić, Nebojsa; Nouri, Nassim; Rahelić, Dario; Stoian, Anca Pantea; Raz, Itamar
Abstract: The COVID-19 pandemic has had a major effect on healthcare during 2020. Current evidence suggests that, while individuals with diabetes and obesity are no more prone to SARS-CoV-2 infection than those without, the risk of hospitalisation if someone has diabetes or obesity and then contracts COVID-19 is three times higher – and 4.5 times higher if they have diabetes and obesity. We assembled a panel of experts from South and East Europe, the Middle East, and Africa to discuss the challenges to management of diabetes and obesity during and post the COVID-19 pandemic. The experience and learnings of this panel cover a heterogeneous patient population, wide range of clinical settings, healthcare organisations, disease management strategies, and social factors. We discuss the importance of timely and effective disease management via telemedicine, providing reassurance and guidance for patients unable or unwilling to visit healthcare settings at this time. We address the use of novel therapies and their role in managing diabetes and obesity during the pandemic, as well as the importance of controlling hypoglycaemia and preventing cardiovascular complications, particularly in vulnerable people. Finally, we consider post-COVID-19 management of diabetes and obesity, and how these learnings and experiences should impact upon future clinical guidelines.